2021
DOI: 10.3390/biomedicines9091256
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Influence Target Gene Expression through Emerging Epigenetic Mechanisms in Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) refers to the pathologic buildup of extra fat in the form of triglycerides in liver cells without excessive alcohol intake. NAFLD became the most common cause of chronic liver disease that is tightly associated with key aspects of metabolic disorders, including insulin resistance, obesity, diabetes, and metabolic syndrome. It is generally accepted that multiple mechanisms and pathways are involved in the pathogenesis of NAFLD. Heredity, sedentary lifestyle, westernized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 134 publications
(157 reference statements)
0
12
0
Order By: Relevance
“…DNA methylation is highly dynamic and changes in response to environmental conditions, personal cellular, and tissue microenvironments ( Hyun and Jung, 2020 ; Pogribna and Hammons, 2021 ). DNA methylation profiles of liver biopsies obtained from patients with NAFLD revealed that hepatic DNA methylation altered in NAFLD patients is an important factor for the pathogenesis of NAFLD and the progression of this disease from simple steatosis to NAFLD ( Zaiou et al, 2021 ). Betaine attenuated HFD-induced hepatic steatosis and triglyceride accumulation in mice by alleviating the methylation of microsomal triglyceride transfer protein (MTTP) and peroxisomal proliferator-activated receptor alpha (PPARα) promoter in the liver ( Wang et al, 2013 ; Wang et al, 2014 ), indicating the crucial relationship between DNA methylation and NAFLD development.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is highly dynamic and changes in response to environmental conditions, personal cellular, and tissue microenvironments ( Hyun and Jung, 2020 ; Pogribna and Hammons, 2021 ). DNA methylation profiles of liver biopsies obtained from patients with NAFLD revealed that hepatic DNA methylation altered in NAFLD patients is an important factor for the pathogenesis of NAFLD and the progression of this disease from simple steatosis to NAFLD ( Zaiou et al, 2021 ). Betaine attenuated HFD-induced hepatic steatosis and triglyceride accumulation in mice by alleviating the methylation of microsomal triglyceride transfer protein (MTTP) and peroxisomal proliferator-activated receptor alpha (PPARα) promoter in the liver ( Wang et al, 2013 ; Wang et al, 2014 ), indicating the crucial relationship between DNA methylation and NAFLD development.…”
Section: Discussionmentioning
confidence: 99%
“…“ Nutriepigenomics” a fast-evolving field that involves the study of nutrient-genome interactions via epigenetic alterations is rapidly gaining prominence in various complex human disorders [ 153 , 154 ]. Food intake influences epigenome remodeling considerably all throughout life.…”
Section: Lifestyle Variables As Dna Methylations Modifiersmentioning
confidence: 99%
“…Epigenetic regulation in NAFLD mainly comprises DNA methylation, histone modifications, and noncoding RNAs [ 9 , 10 , 11 ]. Histone modifications are mediated via the transfer or removal of amino acid residues from the histone tails by some enzymes [ 12 ]. As a form of histone modification, histone demethylation activates or represses gene expression by removing methyl groups from modified histones through histone demethylases (HDMs).…”
Section: Introductionmentioning
confidence: 99%